Flavonoids: Classification, Function, and Molecular Mechanisms Involved in Bone Remodelling - Ramesh, Priyanka; Jagadeesan, Rahul; Sekaran, Saravanan; Dhanasekaran, Anuradha; Vimalraj, Selvaraj (Frontiers in Endocrinology, 2021)
Flavonoids are polyphenolic compounds spotted in various fruits, vegetables, barks, tea plants, and stems and many more natural commodities. They have a multitude of applications through their anti-inflammatory, anti-oxidative, anti-carcinogenic properties, along with the ability to assist in the stimulation of bone formation. Bone, a rigid connective body tissue made up of cells embedded in a minersalised matrix is maintained by an assemblage of pathways assisting osteoblastogenesis and osteoclastogenesis. These have a significant impact on a plethora of bone diseases. The homeostasis between osteoblast and osteoclast formation decides the integrity and structure of the bone. The flavonoids discussed here are quercetin, kaempferol, icariin, myricetin, naringin, daidzein, luteolin, genistein, hesperidin, apigenin and several other flavonoids. The effects these flavonoids have on the mitogen activated protein kinase (MAPK), nuclear factor kappa β (NF-kβ), Wnt/β-catenin and bone morphogenetic protein 2/SMAD (BMP2/SMAD) signalling pathways, and apoptotic pathways lead to impacts on bone remodelling. In addition, these polyphenols regulate angiogenesis, decrease the levels of inflammatory cytokines and play a crucial role in scavenging reactive oxygen species (ROS). Considering these important effects of flavonoids, they may be regarded as a promising agent in treating bone-related ailments in the future.